PENERAPAN KERJASAMA COMPREHENSIVE STRATEGIC PARTNERSHIP (CSP) ANTARA TIONGKOK-INDONESIA DI BIDANG ANTARIKSA PERIODE 2015-2020 - Marini Amimah (2021)
China is one of the leading actors in space technology. This makes China more active in terms of multilateral and bilateral cooperation with countries that have space potential, to spread its influence to the international world. One of them is Indonesia which has potential in the field of space. Therefore, in 2015, the two countries agreed on a Comprehensive Strategic Partnership (CSP) for the period of 2015-2020, which contained points on space cooperation. Using descriptive qualitative research methods, this study aims to determine the implementation of a comprehensive strategic partnership (CSP) between China and Indonesia on space for the 2015-2020 period. The concepts of Bilateral Cooperation, National Interest, and Space Race are used as instruments in conducting this research. The implementation of these eleven areas of cooperation has been carried out well and has benefited both countries, although in each cooperation there are always challenges and obstacles experienced during the process.